TANGGUNG JAWAB PELAKU USAHA TERHADAP KONSUMEN ATAS PENJUALAN EMAS TIDAK SESUAI KADAR EMAS BERDASARKAN HUKUM PERLINDUNGAN KONSUMEN: Business Responsibility For Sale Of Gold Which Is Not According To Gold Content Based On Consumer Protection Law - Zulfikar Hidayat; N.G.N Renti Maharaini (Faculty of Law, Universitas Trisakti, 2025)
The Responsibility of Business Actors to Consumers for Selling Gold Not in Accordance with Promised Gold Content Based on decision No. 8/Pid.Sus/2022/PT BNA, the issue at hand is: What is the responsibility of business actors to consumers for selling gold that does not meet the promised gold content according to Law No. 8 of 1999 on Consumer Protection, and whether Decision No. 8/Pid.Sus/2022/PT BNA regarding business actors selling gold not in accordance with the promised gold content complies with Law No. 8 of 1999 on Consumer Protection. This article discusses the issue using normative research that is descriptive in nature, with library studies analyzed qualitatively to draw conclusions deductively. The results and conclusions indicate that Toko Emas Asia Banda Aceh must take responsibility in accordance with Article 19 paragraph (1) of the law for consumer losses resulting from the sale of gold not matching the promised content by providing compensation in the form of a refund or replacement with equivalent goods or services. Furthermore, Decision No. 8/Pid.Sus/2022/PT BNA is not in accordance with Law No. 8 of 1999 on Consumer Protection because it only imposed criminal sanctions on the business actor Toko Emas Asia Banda Aceh. According to Article 28 of the Consumer Protection Law, judges must provide reverse proof to business actors for consumer losses.